Making an Impact in the Kurdistan Region-Iraq Summary of Four Studies to Assess the Present and Future Labor Market, Improve Technical Vocational Education and Training, Reform the Health Sector, and Build Data Collection Capacity - Anthony, C. Ross (RAND Corporation, 2015)
This executive summary describes key results from four studies carried out by the RAND Corporation in Phase II of its work for the Kurdistan Regional Government (KRG). RAND's work aims to help the KRG expand access to high-quality technical and vocational education and training; improve access to, the quality of, and financing for health care; improve the private sector labor market; and prepare and conduct the Kurdistan Region Labor Force Survey.